Pengaruh Curah Hujan Terhadap Produksi Alat Angkut Batubara PT Bima Nusa Internasional Pit Susubang Jobsite PT Kideco Jaya Agung Kecamatan Muara Komam Kabupaten Paser Provinsi Kalimantan Timur - Nurhidayatullah Am; Shalaho Dina Devy; Lucia Litha Respati; Ardhan Ismail; Tommy Trides; Agus Winarno (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Coal mining in indonesia mostlyuses open pit mining methods. Including coal mines owned by PT Bima Nusa Internasional. Administratively, the research area is located in the muara komam area, batu sopang sub-district, paser district, east kalimantan. Open pit mining is a direct method that is exposed to free air above the surface. This study aims to determine the effect of rainfall on the production of coal hauling equipment at PT Bima Nusa Internasional. High rainfall can affect the performance of coal hauling equipment, which in turn has the potential to disrupt operational smoothness and reduce productivity. This study uses a quantitativeapporach by analyzing daily rainfall data for two months and coal hauling equipmentproduction data for a two months period. The results of the study show that there is a significant negative relationship between rainfall and the amount of coal transport equipment production.